The complete chloroplast genome of Azara serrata (Salicaceae) from Chile - Su, Min (Mitochondrial DNA B Resour, 2018)
The chloroplast (cp) genome sequence of Azara serrata has been characterized from Illumina pair-end sequencing. The complete cp genome was 158,306 bp in length, containing a large single copy region (LSC) of 85,059 bp and a small single copy region (SSC) of 17,889 bp, which were separated by a pair of 27,679 bp inverted repeat regions (IRs). The genome contained 129 genes, including 85 protein-coding genes, 36 tRNA genes, and 8 rRNA genes. The overall GC content is 36.5%, while the corresponding values of the LSC, SSC, and IR regions are 34.3, 30.0, and 42.0%, respectively. Further, phylogenetic analysis suggested that the A. serrata is a sister of Flacourtia indica and is an outgroup to the remaining genera of Saliaceae.